ARTIFICIAL INTELLIGENCE AND MULTIMEDIA TECHNOLOGIES IN THE DEVELOPMENT OF UNIVERSITY STUDENTS’ FOREIGN LANGUAGE COMMUNICATIVE COMPETENCE - Жакаева Гулсина Кочкорбаевна; Семетеева Канайым Семетеевна (TILSHUNOSLIK VA CHET TILLARNI O‘QITISHDA ZAMONAVIY RAQAMLI TEXNOLOGIYALARDAN FOYDALANISH MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
The article examines the role of multimedia technologies and artificial intelligence in the development of university students’ foreign-language communicative competence. The study analyzes the current state of this methodological issue by focusing on the benefits of multimedia technologies in language education, the difficulties associated with integrating digital educational resources into higher education, as well as the pedagogical conditions and characteristics that determine their effectiveness in foreign language teaching. Particular attention is paid to the didactic potential of digital educational resources (DERs) used in English language instruction at universities, including learning management systems (LMS), social media platforms, cloud-based technologies, mobile applications, and AI-powered systems. The paper also explores the prospects of implementing such LMS platforms as Moodle and Edvibe in higher education by analyzing their functional features, advantages, and limitations. In addition, the study evaluates the current application of AI-based tools in university education. Special emphasis is placed on platforms such as ChatGPT, Midjourney, Gemini, and Microsoft 365 Copilot, which can be effectively utilized in foreign language teaching practices. The findings highlight the importance of developing a digital educational environment capable of integrating diverse multimedia tools for the effective formation of students’ foreign-language communicative competence while taking into account individual learning needs. The article also stresses the necessity of improving digital literacy among all participants in the educational process, particularly in relation to the use of AI technologies in foreign language teaching and learning.